Attributes of a State-Owned Enterprise as a Legal Entity - KULIKOVA, A. A.; NORBEKOVA, J. S. (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The article considers such legal entity attributes of a state enterprise as: organizational unity; property isolation; ability to acquire, possess and exercise property rights and responsibilities on its own behalf, and to bear property liabilities for its obligations as well; ability to act in jurisdictional bodies on its own behalf. Special attention is paid to the subsidiary liability characteristics, specific for a state enterprise.